A Novel Psychosocial Intervention for Motivational Negative Symptoms in Schizophrenia: Combined Motivational Interviewing and CBT - Reddy, L Felice; Glynn, Shirley M; McGovern, Jessica E; Sugar, Catherine A; Reavis, Eric A; Green, Michael F (The American journal of psychiatry, 2023)
Negative symptoms are a primary cause of disability in schizophrenia for which there are no established pharmacotherapies. This study evaluated a novel psychosocial intervention that combined two evidence-based practices-motivational interviewing and cognitive-behavioral therapy (MI-CBT)-for the treatment of motivational negative symptoms. Seventy-nine participants with schizophrenia and moderate to severe negative symptoms were included in a randomized controlled trial comparing the 12-session MI-CBT treatment with a mindfulness control condition. Participants were assessed at three time points through the study period, which included 12 weeks of active treatment and 12 weeks of follow-up. The primary outcome measures were motivational negative symptoms and community functioning; the secondary outcomes included a posited biomarker of negative symptoms: pupillometric response to cognitive effort. Compared with the control group, participants in the MI-CBT group showed significantly greater improvements in motivational negative symptoms over the acute treatment period. Their gains relative to baseline were maintained at follow-up, although the differential benefit relative to control subjects was attenuated. There were nonsignificant effects toward improvements in community functioning and differential change in the pupillometric markers of cognitive effort. The results show that combining motivational interviewing with CBT yields improvements in negative symptoms, a feature of schizophrenia generally thought of as resistant to intervention. Motivational negative symptoms not only responded to the novel treatment, but the gains were maintained over the follow-up period. Implications for future studies and for improving the generalization of the negative symptom gains to daily functioning domains are discussed.